Using Action Research and Peer Perspectives to Develop Technology That Facilitates Behavioral Change and Self-Management in COPD - Dinsmore, John; Mc Cabe, Catherine; O'Donnell, Sharon; Brady, Anne-Marie; Mc Kee, Gabrielle (My University, 2014)
Background. Behavioural change and self-management in patients with chronic illness may help to control symptoms, avoid rehospitalization, enhance quality of life, and decrease mortality and morbidity. Objective. Guided by action research principles and using mixed methods, the aim of this project was to develop peer based educational, motivational, and health-promoting peer based videos, using behavioural change principles, to support self-management in patients with COPD. Methods. Individuals (n = 32) living with COPD at home and involved in two community based COPD support groups were invited to participate in this project. Focus group/individual interviews and a demographic questionnaire were used to collect data. Results. Analysis revealed 6 categories relevant to behavioural change which included self-management, support, symptoms, knowledge, rehabilitation, and technology. Participants commented that content needed to be specific, and videos needed to be shorter, to be tailored to severity of condition, to demonstrate “normal” activities, to be positive, and to ensure that content is culturally relevant. Conclusions. This study demonstrated that detailed analysis of patient perspectives and needs for self-management is essential and should underpin the development of any framework, materials, and technology. The action research design principles provided an effective framework for eliciting the data and applying it to technology and testing its relevance to the user.
PUBLISHED
Keywords: Chronic obstructive pulmonary disease (COPD); Ageing; Creative Technologies; Digital Engagement; Identities in Transformation